Understanding the challenges and coping mechanisms adopted by nursing staff in managing critically-ill patients at district hospitals in the Ashanti Region, Ghana - Akua Kusiwaa Karikari; Peter Agyei-Baffour; Charles Mock; Anthony Kwaku Edusei; Peter Donkor; Isaac Kofi Yankson; Gifty Akua Merdiemah (Elsevier, 2023)
Many hospitals that manage health emergencies are resource-constrained and as such have challenges to provide quality care to patients. Exploring these challenges in resource-constrained hospitals and addressing them at the operational level through coping mechanisms could aid timely interventions to save patients with potentially life-threatening conditions. The study adopted qualitative approach and grounded theory design. Simple random sampling was used to cluster selected hospitals while purposive sampling was used to select right cadre of nursing leaders with experience to provide needed information. Data collection was done through interviews. Findings indicate nursing staff face a myriad of challenges including logistics, human resources, knowledge, financial resources, staff attitude and professional barriers in managing critically-ill patients. The findings also indicate that, identified challenges have resulted in increased workload, job dissatisfaction among staff, and some negative consequences on the safety and health care outcomes of patients. The most important recommendation from the participants is increasing the availability of in-service emergency training to improve skill levels of nurses and patient outcomes.